Are we waking up to the effects of NEFA? - Jun, Jonathan C. (Diabetologia, 2015)
NEFA are mobilised from adipose tissues during fasting or stress. Under conditions of acute or chronic NEFA excess, skeletal muscle and hepatic insulin resistance may ensue. Hence, a wealth of literature has focused on the crosstalk between NEFA and glucose in the pathogenesis of insulin resistance. Sleep restriction has also been shown to acutely induce insulin resistance, and self-reported short sleep duration is associated with diabetes. In this issue of Diabetologia (DOI: XXX), Broussard and colleagues examine the impact of acute sleep restriction on detailed 24 h metabolic profiles, including plasma NEFA. Here, we address the potential clinical relevance of these findings and pose questions for further research.